FAKTOR YANG MEMPENGARUHI PELAKSANAAN INISIASI MENYUSU DINI (IMD) - Arefti, Vyola Chania; Rahmadani, Risna Ayu; Susanti, Susanti; Sendra, Eny; Indriani, Ririn (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Abstract: Early initiation of breastfeeding can prevent 22% of infant deaths in developing countries by 28 months of age, but if breastfeeding is first, when the baby is over two hours old and under the first 24 hours, it can prevent 16% of infant deaths under 28 days. The coverage of early breastfeeding initiation at Syekh Yusuf Hospital in 2022 was only 66%. The purpose of the study was to determine the factors that influence the implementation of early breastfeeding initiation (IMD). The type of research is quantitative with a cross sectional approach. The research was conducted at Sheikh Yusuf Hospital. The sample amounted to 64 people. The sampling technique used in this study was total sampling. Data analysis was done univariate and bivariate. The results of the analysis showed there was a relationship between habit (p value: 0.004) to the practice of early breastfeeding initiation. It is recommended for the Health Office, to increase promotion about IMD, and for RSUD Sheikh Yusuf Kab, Gowa to make policies for health workers to carry out IMD according to procedures. Carry out monitoring and evaluation and monitor the implementation of Early Breastfeeding Initiation. Health workers should be able to encourage the mother's family to support the implementation of IMD correctly.Keywords: IMD, Habits, Promotion